Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India - Sumod, K. S.; Hibino, Yusuke; Manjabrayakath, Hashim; Sanjeevan, V. N. (Zootaxa, 2019)
A deep-sea species of snake eel (family Ophichthidae, subfamily Ophichthinae) Ophichthus mccoskeri sp. nov. is described based on 6 specimens (331–447 mm total length) trawled at 314–363 m depth in Andaman waters, India. This species is differentiated from its deep-water congeners by a combination of characters such as its large eyes, dorsal-fin origin a short distance behind pectoral-fin tip, anal fin black posteriorly, three preopercular pores, maxillary and mandibular teeth ending as triserial, and in a vertebral formula of 20/55/153.